Teacher well-being and turnover intention among teachers: A systematic review - Cathlin, Cintya Amelia; Saleh, Airin Yustikarini; Meidelina, Olga; Winesa, Sekar Aulia (Buletin Psikologi, 2025)
Teaching is a profession that requires high dedication and commitment due to the heavy workloads and responsibilities. There has been a trend of turnover intention among teachers that results from the undervaluation and underappreciation of the profession. Schools have to manage teacher turnover since it impacts student outcomes, teacher well-being, and school performance. This systematic review aimed to summarize the findings of teacher turnover intention and its impacts on teacher well-being and explore well-being factors that influence teachers’ decisions to remain in the profession. The review was done following PRISMA guidelines with 11 articles published from 2013 to 2024. The studies consistently show that higher well-being is associated with lower desire to leave the profession. The implications of this study emphasize the need for systemic interventions to enhance teacher well-being and keep teachers in their roles, which will benefit the broader education sector.